Pendampingan Pendidikan Desa: “Kampung Menari” (Membangun Generasi Muda Hingga Pelosok Negeri) - Ary Suharyanto; Dyah Mutiarin; Rizky Dwi Lestari (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2021)
This empowerment program aims to identify programs that are relevant to be implemented and describe the results that have been carried out by actors in overcoming educational problems after the Covid-19 Pandemic in Pogalan Village, Pakis District, Magelang Regency. The empowerment implementation methods include Motivation Class, Main Lesson Mentoring, Focus Group Discussion Supporting System, and Hamlet Library Development. The results of empowerment include: Increased knowledge and motivation of school children to continue their education to a higher level; increasing student scores in the subjects that are mentored; increased support for the children's education system, especially from parents and school teachers; and the availability of a village library which is a place to increase children's literacy. The empowerment carried out by Mata Garuda LPDP is a comprehensive effort because it starts with an assessment of the needs of the local community, then the appropriate program is given to each target..